Size-controlled synthesis of ZnO nanorods for highly sensitive NO\(_2\) gas sensors - Minh, Luu Hoang; Thu, Pham Thi Thuy; Tuan, Luong Minh; Thanh, Bui Quang; Hue, Mai Thi; Tho, Ta Thi; Tong, Pham Van (Communications in Physics, 2023)
The nanostructure of zinc oxide has excellent potential in gas sensing applications to detect and monitor toxic gases in the atmosphere. Appropriate nanostructures can enhance the performance of gas sensors. In this study, we report the controlled fabrication of ZnO nanorods of different sizes by a simple hydrothermal method, which can be applied to detect NO2 toxic gas efficiently. The size of the nanorods was controlled by varying the amount of D-Glucose. The morphology and crystal structure of the materials were analyzed using advanced techniques such as field-emission scanning electron microscopy, X-ray diffraction patterns, and energy-dispersive X-ray spectroscopy. The sensor's response based on ZnO nanorods at 2 ppm NO2 is 13.3 and 18.8 times higher than that of 500 ppm CO and NH3, respectively. In addition, the sensor also exhibits good selectivity and repeatability for NO2 toxic gas; The optimum working temperature is about 150 oC.\[H_2= H_1+ H_1 \tag{1}\] H2 hoac H2